Art therapy and postmodernism : creative healing through a prism. - Burt, Helene (Jessica Kingsley Publishers, 2011)
This comprehensive book brings together the voices of international art therapists with diverse backgrounds and experiences and asks them to consider the role of postmodernism in their understanding of art therapy. These practitioners share a common postmodern belief that art is a unique way of expressing and mediating the human condition and that art therapy should not be a diagnostic tool but a collaborative healing process between the therapist and the client. Drawing on psychotherapy, aesthetics and philosophy, the contributors present current practice, research and case studies and show t.